The Significant Influence of Tour Guides' Roles as Experience Creators on Foreign Tourists' Memorable Tourism Experiences in Bromo Tengger Semeru National Park - Prayoga, Tegar (Jurnal Ragam Pengabdian, 2026)
Purpose this research investigates the significant influence of the tour guide’s role as an Experience Creator on foreign tourists' Memorable Tourist Experience (MTE) within the extreme and highly volatile environment of Bromo Tengger Semeru National Park (TNBTS). Research methods, the study utilized a quantitative explanatory approach with a cross-sectional design. Primary data were systematically collected via self-administered digital questionnaires (utilizing QR codes to mitigate social desirability bias) from a sample of 100 guided foreign tour-ists, determined by the Lemeshow formula. The unidimensional facilitation framework was statistically evaluat-ed using Simple Linear Regression Analysis via SPSS. Results and discussion, empirical findings revealed that the tour guide's role as an Experience Creator exerts a highly significant positive influence on the MTE (t-count = 10.386, p < 0.05), explaining 52.4% of the variance in experience quality. The research establishes that a guide's journey and setting management function as critical cognitive load reducers, while their interpersonal capability acts as an emotional catalyst. Conclusively, logistical mastery and active environmental orchestration by tour guides are absolute prerequisites for profound memory formation in extreme natural destinations, superseding conventional historical storytelling.